Cluster analysis and data mining : an introduction - King, Ronald S., 1943- (Mercury Learning and Information, 2015)
Cluster analysis is used in data mining and is a common technique for statistical data analysis used in many fields of study, such as the medical & life sciences, behavioral & social sciences, engineering, and computer sciences. This book is applicable to either a course on clustering and classification or as a companion text for a first class in applied statistics. This book puts emphasis on illustrating the underlying logic in making decisions during the cluster analysis; brings out the related applications of statistics: Ward's method (ANOVA), JAN (regression analysis & correlational analysis), cluster validation (hypothesis testing, goodness-of-fit, Monte Carlo simulation, etc.); and includes separate chapters on JAN and the clustering of categorical data. --